The Teachers of Quality Academy: Evaluation of the Effectiveness and Impact of a Health Systems Science Training Program. - Walsh, Danielle S.; Lazorick, Suzanne; Lawson, Luan; Lake, Donna; Garrison, Herbert G.; Higginson, Jason; Vos, Paul; Baxley, Elizabeth (American Journal of Medical Quality)
This project aimed to evaluate the effectiveness of a faculty development program in health systems science (HSS)-the Teachers of Quality Academy (TQA). Participants in TQA and a comparison group were evaluated before, during, and 1 year after the program using self-perception questionnaires, tests of HSS knowledge, and tracking of academic productivity and career advancement. Among program completers (n = 27), the mean self-assessed ratings of knowledge and skills of HSS topics immediately after the program, as compared to baseline, increased significantly compared to controls (n = 30). Participants demonstrated progressive improvement of self-perceived skills and attitudes, and retention of HSS knowledge, from baseline to completion of the program. Participants also demonstrated substantially higher HSS scholarly productivity, leadership, and career advancement compared to the comparison group. The TQA effectively created a faculty cadre able to role model, teach, and create a curriculum in HSS competencies for medical students, resident physicians, and other health professionals.